The effects of nicotine administration on the pathophysiology of rat aortic wall. (17th February 2017) - Kugo, H; Zaima, N; Tanaka, H; Urano, T; Unno, N; Moriyama, T
Abstract: Abdominal aortic aneurysm (AAA) is the progressive dilation of the abdominal aorta. Nicotine is reported to be associated with the development and rupture of AAA, but the pathological effects of nicotine on normal rat aorta have not been determined. We investigated pathological changes in the aortic wall of rats caused by the administration of nicotine. Nicotine administration weakened the vascular wall, increased gelatinolytic activity and promoted the destruction of elastin and collagen in the rat abdominal aorta. There were no differences in the areas positive for matrix metalloproteinase (MMP)-2 and MMP-9 between the control and nicotine treated groups. The areas positive for MMP-12 in the nicotine group were significantly greater than for the control group. Gelatinolytic activity in the aortic wall was increased significantly in the nicotine group. Our findings suggest that MMP-12 is sensitive to nicotine exposure in rats.